Biodiversity and ecosystem services in forest ecosystems: a research agenda for applied forest ecology. Issue 1 (9th May 2016) - Mori, Akira S.; Lertzman, Kenneth P.; Gustafsson, Lena
Summary: Given the substantial contributions of forest biodiversity and ecosystem services to society, forest sciences have a large potential to contribute to the integrity and sustainability of our future. This is especially true when the roles of biodiversity for sustaining ecosystem services are considered. The rapid expansion of sustainable forest management (SFM) has resulted in the adoption of various forest management frameworks intended to safeguard biodiversity. Concurrently, the importance of forest ecosystem services has been increasingly recognized. Although some initiatives aimed at conserving both biodiversity and ecosystem services are emerging, knowledge gaps still exist about their relationships and potential trade‐offs in forests. Given recent advancements, increasing opportunities and some lags in forest ecology, further research on biodiversity, ecosystem functions and services will play substantial roles in the development of SFM practices. Here, we identified key issues including (i) relationships between biodiversity and ecosystem function as a foundation of ecological integrity, (ii) resilience thinking to better prepare for and adapt to environmental changes, (iii) social–ecological perspectives that facilitate real‐world conservation and management and (iv) theory‐driven restoration that bridges science and practice. Thus, we illustrate priorities and future possibilities in applied ecology studies in forests, which will help society and ecosystems to build capacity and resilience to face uncertainty in the changing environment. Synthesis and applications . Under substantial human influences, forests are highly likely to be largely altered, potentially leading to the emergence of novel ecosystems or alternative stable states. Management thus needs more flexible, novel measures to address the significant uncertainty this generates. Resilience‐based approaches are important to respond adaptively to future changes and cope with surprises, potentially providing multiple options. Although challenges exist, theory should play an important role in managing, conserving and restoring forest ecosystems. The issues discussed here should receive further attention in the context of the multiple goals of sustainable forest management.